Inhibitory Receptor Trap: A Platform for Discovery of Inhibitory Receptors That Utilize Inositol Lipid and Phosphotyrosine Phosphatase Effectors - Crute, Bergren W.; Sheraden, Rachel; Ott, Vanessa L.; Harley, Isaac T. W.; Getahun, Andrew; Cambier, John C. (Frontiers in Immunology, 2020)
Among the areas of most impactful recent progress in immunology is the discovery of inhibitory receptors and the subsequent translation of this knowledge to the clinic. Although the original and canonical member of this family is FcRIIB, more recent studies defined PD1 as an inhibitory receptor that constrains T cell immunity to tumors. These studies led to development of “checkpoint blockade” immunotherapies (CBT) for cancers in which PD1 interactions with its ligand are blocked. Unfortunately, although very effective in some patients, only a small proportion respond to this therapy. This suggests that additional as yet undescribed inhibitory receptors exist which could be exploited. Here we describe a new platform, termed Inhibitory Receptor Trap (IRT), for discovery of members of this family. The approach takes advantage of the fact that many of the known inhibitory receptors mediate signaling by phospho-Immunoreceptor Tyrosine-based Inhibition Motif (ITIM) mediated recruitment of Src Homology 2 (SH2) domain-containing phosphatases including the SH2 domain-containing Inositol Phosphatase SHIP1 encoded by the INPP5D gene and the SH2 domain-containing phosphotyrosine Phosphatases SHP1 and SHP2 encoded by the PTPN6 and PTPN11 genes respectively. Here we describe the IRT discovery platform in which the SH2 domains of inhibitory phosphatases are used for affinity-based isolation and subsequent identification of candidate effectors via immunoblotting and high sensitivity liquid chromatography-mass spectrometry. These receptors may represent alternative targets that can be exploited for improved CBT. Salient observations from these studies include the following: SH2 domains derived from the respective phosphatases bind distinct sets of candidates from different cell types. Thus cells of different identity and different activation states express partially distinct repertoires of up and downstream phosphatase effectors. Phosphorylated PD1 binds not only SHP2 but also SHIP1, thus the latter may be important in its inhibitory function. B cell antigen receptor signaling leads predominantly to CD79 mono-phosphorylation as indicated by much greater binding to Lyn SH2 than Syk (SH2)2. This balance of ITAM mono- versus bi-phosphorylation likely tunes signaling by varying activation of inhibitory (Lyn) and stimulatory (Syk) pathways.